2016
DOI: 10.5209/rev_rccv.2016.v10.n1.52501
|View full text |Cite
|
Sign up to set email alerts
|

Niveles de glucosa y triglicéridos en plasma seminal y motilidad espermática en COBAYOS alimentadas con 10% más en energÍa digestible

Abstract: RESUMENEl objetivo del presente estudio fue determinar los niveles de los componentes energéticos (glucosa y triglicéridos) en el plasma seminal y la motilidad espermática de 10 cobayos, los cuales fueron alimentados por un período de 2 meses con una dieta 10% mayor en energía digestible (ED). El nivel de glucosa encontrado en plasma seminal fue de 11.59 ± 0.5 mg/dL y el valor de triglicéridos fue de 55.95 ± 3.2 mg/dL, mientras que la motilidad promedio fue de 95%. Concluimos que en cobayos los niveles de gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(10 reference statements)
1
0
0
Order By: Relevance
“…Guinea pig spermiogram studies show variable concentrations and motility rates depending on the method of extraction and analysis. In spermatozoa from the epididymis, as in this study, Ayala Guanga et al [21] reported 418.0 × 10 6 /mL and 58% motility, Rodríguez et al [22] reported 95% motility, and Ferdinand et al [23] reported 149.85 × 10 6 /mL sperm concentration. Using electroejaculation, the values are generally low, ranging from 36.70 to 47.33 × 10 6 /mL for concentration and 49.49 to 90.86% for individual motility [14,24,25].…”
Section: Discussionsupporting
confidence: 68%
“…Guinea pig spermiogram studies show variable concentrations and motility rates depending on the method of extraction and analysis. In spermatozoa from the epididymis, as in this study, Ayala Guanga et al [21] reported 418.0 × 10 6 /mL and 58% motility, Rodríguez et al [22] reported 95% motility, and Ferdinand et al [23] reported 149.85 × 10 6 /mL sperm concentration. Using electroejaculation, the values are generally low, ranging from 36.70 to 47.33 × 10 6 /mL for concentration and 49.49 to 90.86% for individual motility [14,24,25].…”
Section: Discussionsupporting
confidence: 68%